2021
DOI: 10.3390/cancers13051156
|View full text |Cite
|
Sign up to set email alerts
|

The Two-Faced Role of SIRT6 in Cancer

Abstract: Sirtuin 6 (SIRT6) is a NAD+-dependent nuclear deacylase and mono-ADP-ribosylase with a wide spectrum of substrates. Through its pleiotropic activities, SIRT6 modulates either directly or indirectly key processes linked to cell fate determination and oncogenesis such as DNA damage repair, metabolic homeostasis, and apoptosis. SIRT6 regulates the expression and activity of both pro-apoptotic (e.g., Bax) and anti-apoptotic factors (e.g., Bcl-2, survivin) in a context-depending manner. Mounting evidence points tow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 123 publications
0
35
0
Order By: Relevance
“… 6 Further investigations indicated that SIRT6 knockout in MEFs leads to tumorigenesis without activation of known oncogenes, and deletion of SIRT6 in vivo correlates with an increased number, size, and aggressiveness of tumors ( Figure 4 ). 8 , 11 The tumor-suppressor role of SIRT6 was associated with the suppression of glycolytic genes crucial for the Warburg effect, a metabolic shift common in cancer cells where ATP is obtained mostly through glycolysis rather than mitochondrial oxidative phosphorylation, in order to generate immediate energy to support fast proliferation and related cellular processes. 58 These genes, including the glucose transporter-1 (GLUT1), lactate dehydrogenase (LDH), phosphofructokinase-1 (PFK1), and pyruvate dehydrogenase kinase-1 (PDK1), are regulated by the hypoxia-inducible factor 1α (HIF-1α), which is corepressed by SIRT6.…”
Section: Biological Functions and Disease Relevance Of Sirt6mentioning
confidence: 99%
See 2 more Smart Citations
“… 6 Further investigations indicated that SIRT6 knockout in MEFs leads to tumorigenesis without activation of known oncogenes, and deletion of SIRT6 in vivo correlates with an increased number, size, and aggressiveness of tumors ( Figure 4 ). 8 , 11 The tumor-suppressor role of SIRT6 was associated with the suppression of glycolytic genes crucial for the Warburg effect, a metabolic shift common in cancer cells where ATP is obtained mostly through glycolysis rather than mitochondrial oxidative phosphorylation, in order to generate immediate energy to support fast proliferation and related cellular processes. 58 These genes, including the glucose transporter-1 (GLUT1), lactate dehydrogenase (LDH), phosphofructokinase-1 (PFK1), and pyruvate dehydrogenase kinase-1 (PDK1), are regulated by the hypoxia-inducible factor 1α (HIF-1α), which is corepressed by SIRT6.…”
Section: Biological Functions and Disease Relevance Of Sirt6mentioning
confidence: 99%
“…If we take into account the involvement of SIRT6 in DNA-damage repair, depending on the stage of cancer progression, this pathway may have tumor-promoting or tumor-suppressing effects. 11 Moreover, high levels of SIRT6 associated with tumors may also represent a compensating response rather than a causality. Therefore, it is vital to distinguish the potential of SIRT6 as a therapeutic target or as a biomarker in each type of tumor.…”
Section: Biological Functions and Disease Relevance Of Sirt6mentioning
confidence: 99%
See 1 more Smart Citation
“…SIRT6 is found overexpressed in skin cancer and non-small cell lung cancer (NSCLC) [163,164], osteosarcoma, colon carcinoma, serous ovarian cancer and in clear cell renal cell carcinomas (ccRCC) [164][165][166][167][168], showing poor prognostic value. However, in certain types of cancer SIRT6 is classified as a tumor suppressor.…”
Section: Sirtuin Inhibitors Addressing Roles Of Marylating Sirtuins In Cancermentioning
confidence: 99%
“…SIRT6 associates in a phosphorylationdependent form with Ras-GTPase activating protein 1 (G3BP1) [172], with transcription factors BCLAF1, NKRF and THRAP3, the telomerase regulator YLPM1, and the RNA polymerase complex factors COIL and XRN2. The development of small molecules inhibiting specifically either deacetylation or MARylation may provide new clues on SIRT6 functions [178,179,163].…”
Section: Sirtuin Inhibitors Addressing Roles Of Marylating Sirtuins In Cancermentioning
confidence: 99%